A Collaboration of Surface Protection and Bulk Doping for High‐performance Li‐rich Cathode Materials. Issue 20 (28th May 2019) - Wang, Min‐Jun; Yu, Fu‐Da; Sun, Gang; Gu, Da‐Ming; Wang, Zhen‐Bo
Abstract: Li‐rich layered oxides (LLRO) are promising high energy‐density cathode, but always suffer from the oxygen loss in initial activation and gradual structure transformation during cycling, which leads to capacity degradation and potential decay. Here, we employ a simple strategy to achieve the collaboration of surface protection and bulk doping for improving the performance of Li‐rich material. Scanning electron microscope and transmission electron microscopy tests demonstrate that a nanoscale protective layer of magnesium pyrophosphate is uniformly coated on the Li‐rich material surface. X‐ray diffraction test indicates Mg 2+ and P2 O7 4− are incorporated into the crystal structure, which induces the larger lattice spacing and lower cation mixing. As a result, the resultant LLRO displays extremely high Coulombic efficiency of 91.8% and discharge capacity of 288.4 mAh g −1, showing prominent cycling stability of 89.2% after 200 cycles. Furthermore, our strategy also suppresses the attenuation of average voltage during cycling and the potential drop is only 0.56 mV per cycle from 25 th to 200 th cycle. The excellent electrochemical performance can be ascribed to the combined merits of surface protection and bulk doping. This strategy may provide some new insights into the design and synthesis of high‐performance electrode materials. Abstract : Pyrophosphate as a complexing agent, can control reaction rate of precipitation process effectively, and helps to form an ultrathin coating layer of magnesium pyrophosphate on Li‐rich material surface. Follow‐up high‐heat treatment facilitates incorporation of Mg 2+ and P2 O7 4− into crystal structure of Li‐rich material. This strategy achieves the collaboration of surface protection and bulk doping, and improves electrochemical performance integrally.